Excel Solver dengan Evolutionary Algorithm sebagai alternatif penyelesaian Capacitated Vehicle Routing Problem (CVRP) - Sanggala, Ekra; Sulistiyaningsih, Febriani; Nirwan, Saepudin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The Capacitated Vehicle Routing Problem (CVRP) is one of the most popular variants of VRP. In CVRP, only the mass of objects to be transported is considered, typically assuming they are of the same type. Evolutionary Algorithm (EA) is a metaheuristic that can be applied to various optimization problems, including CVRP. Solver is an Excel Add-In that is capable of running EA. With the ability of Evolutionary Algorithm to tackle CVRP and the Solver which is capable of running EA, it can be concluded that solving CVRP can be done using the Solver. For instance A-n32-k5, the solution generated by Solver with EA is 824 or 5.1% longer than the Best Known Solution.